Thrombocytopenia in Neonatal Intensive Care Unit and Role of Platelet Transfusion - Noshina Noreen, Samina T. Amanat,Sundas Ali , Noshina Noreen, Samina T. Amanat,Sundas Ali (Journal of Rawalpindi Medical College, 2019)
Background: To determine frequency of thrombocytopenia in NICU and to find outcome of neonates receiving multiple platelet transfusion Methods: In this cross sectional study, neonates with thrombocytopenia , admitted to neonatal intensive care unit (NICU) were included. Two milliliter of blood was collected in EDTA bottle and kept on a roller mixer for mixing until a platelet count done by automated haematology analyzer. Stained film was examined under light microscope to rule out platelet clumps and to ensure that platelets had been spread evenly before actual count was done. At least two platelet readings were taken during admission. Platelets were transfused to neonates at platelet count less than 50,000. Any mortality in neonates receiving platelet transfusion was recorded during hospital stay. Results:The mean age of neonates was 2.92±2.20 days, 63.2% were male and 36.8% were females. Thrombocytopenia was present in 41.4%, percentage of neonates. Platelet transfusions were administered to 12.7% and recorded mortality was 4.5%. Conclusion: Thrombocytopenia in neonates at NICU is higher while the outcome of neonates receiving platelet transfusion is appreciable.